Hubungan Sistem Promosi Dengan Motivasi Kerja Pegawai Di Sekretariat Daerah Kabupaten Halmahera Selatan - Puka-Puka, Marlina; Rorong, Arie Junus; Ruru, Joorie Marhaen (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACTThe purpose of this study was to determine the relationship between the system of promotion andmotivation of employees working in the Secretariat of the South Halmahera District.This study uses a quantitative method that is associative. Sample of respondents were taken byproportional random sampling technique as many as 50 people or about 52% of the population (97 peoplePNS) Regional Secretariat of South Halmahera. Collecting data using questionnaires / questionnaire andassisted with interview techniques. The analysis technique used is descriptive statistical analysis is theanalysis of the frequency distribution and percentage, as well as analaisis chi-square and contingencykooefisien.Based on the analysis of data drawn conclusions: (1) System promotion of civil servants in SouthHalmahera District Secretariat is generally performed quite well in accordance with the criteria / basicpromotional applicable, objectively, fairly, and accurately. (2) The level of employee motivation is generallyquite good. (3) There is a significant correlation between promotion and motivation system of employeesworking in the Secretariat of the South Halmahera District; that the better the promotion system is gettingbetter or increase the motivation of the employment.Based on the conclusions of this study it can be suggested: (1) The employee promotion system stillneeds to be improved, especially in terms of the consistency of the use of criteria/ basic promotion,objectivity, and fairness; (2) work motivation of employees still need to be improved; (3) The promotionsystem let be used as one tool to increase employee motivation.Keywords: Promotion System, Work Motivation.